Conference Summary: Agricultural Successes for the Greater Horn of Africa - New Partnership for Africa's Development (NEPAD, 2005)
This conference focused on three principal objectives: a) summarizing key opportunities and challenges for agriculture in the Greater Horn of Africa; b) identifying key successes in expanding African agriculture and improving food security...